Conservatives and right radicals in interwar Europe - Bresciani, Marco 1977- HerausgeberIn (Routledge studies in fascism and the far right, 2021)
"Laboratory for World Destruction": The Habsburg Monarchy and Fascism / Steven Beller -- Volksdeutsch Revisionism: East Central Europe's Ethnic Germans and the Order of Paris / Gregor Thum -- Conservative and Radical Dynamics of Italian Fascism: An (East) European Perspective (1918-1938) / Marco Bresciani -- The Crisis of Legitimacy and the Rise of the Radical Right in Interwar Yugoslavia (1918-1941) / Mark Biondich -- Integral Nationalism in Absence of Nation-State: The Case of Ukraine / Oleksandr Zaitsev -- Catholic Authoritarians or Fascists as Such? The Polish Rightist Subculture Turns Fascist (1919-1939) / Grzegorz Krzywiec -- Faith, Family and Fatherland: Conservatism and Right Radicalism in Interwar Hungary / Béla Bodó -- The Romanian Right: Images of Crisis, the Press and the Rise of Fascism / Roland Clark -- Nationalism and Authoritarianism in Interwar Greece (1922-1940) / Spyridon G. Ploumidis -- Dynamics of Division: The French Right (1918-1941) / Sean Kennedy -- Consecrating the Fatherland: Catholicism, Nationalism and Fascism in Spain (1919-1939) / Giorgia Priorelli and Alejandro Quiroga -- In the Mirror of Fascism: Portugal and the Italian Experience / Giulia Albanese -- America as Alternative to European Radicalism? The United States and the Information Classification: General Transnational Rise of the Right / Kiran Klaus Patel -- Fascism After Fascism: History and Politics / Guido Franzinetti.